PENGARUH SIKAP, PERTIMBANGAN PASAR KERJA, DAN PERSEPSI MENGENAI MASA STUDI PADA NIAT MAHASISWA MENGIKUTI PPAk - Risanti Darmawan, Gusti Ayu Kade; Wirama, Dewa Gede (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.12.NO.01.TAHUN.2023DO - 10.24843/EEB.2023.v12.i01.p07, 2023)
The aims of this study is to provide empirical evidence regarding the effect of attitudes, job market considerations, and perceptions length of study on the intentions of accounting students to take accounting profession educations. Quantitative methods with the distribution of questionnaires related to the measurement of variables are used in this research. The population in this research amounted to 814 students. By taking samples using the non-probability sampling method, a sample of 240 respondents was obtained. The data analysis used in this research is multiple linear regressionnanalysis. The results indicate that attitudes, labor market considerations, and perceptions length of study have positive effects on the intentions of accounting students to enrollin accounting profession education. These findings support the theory of planned behavior.